ADAPTASI SOSIAL BUDAYA MAHASISWA ETNIS BATAK TOBA DALAM LINGKUNGAN MULTIKULTURAL DI UNIVERSITAS NEGERI SEMARANG (UNNES) - Kurniasari, Vita; Sulistyo Rini, Hartati (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study examines the socio-cultural adaptation of Toba Batak ethnic students at Universitas Negeri Semarang (UNNES) within a multicultural campus environment. The research aims to analyze the socio-cultural characteristics of Toba Batak students, identify the challenges encountered in social interactions, and explore the adaptation strategies they employ in daily campus life. This study uses a qualitative method with a phenomenological approach to understand the subjective experiences of students in facing cultural differences. Data were collected through observation, in-depth interviews, and documentation involving Toba Batak students and students from other ethnic backgrounds at UNNES. The analysis applies George Herbert Mead’s Symbolic Interactionism theory to understand how identity and meaning are formed through social interaction. The findings indicate that Toba Batak students maintain strong socio-cultural identities reflected through clan affiliation, communication style, and cultural values brought from their home environment. In the multicultural setting of UNNES, they experience several challenges, including difficulties in understanding the Javanese language, communication misunderstandings caused by differences in speaking styles, and differences in culinary habits. To overcome these challenges, students actively develop adaptation strategies such as learning local language expressions, adjusting communication styles to suit the surrounding culture, and adapting eating habits by seeking alternative foods or cooking independently. The study demonstrates that socio-cultural adaptation is a dynamic process that allows students to maintain their cultural identity while simultaneously adjusting to a diverse social environment. This research contributes to the development of sociological and anthropological studies concerning cultural adaptation among ethnic minority students in higher education.